Pengaruh Profitabilitas, Likuiditas dan Ukuran Perusahaan Terhadap Abnormal Return - Mufida, Eva Layla; Tumirin, Tumirin (Journal of Culture Accounting and Auditing, 2025)
The aim of this research is to determine the effect of return on equity, liquidity and company size on abnormal returns. This type of research is quantitative research using secondary data. This research data collection method uses the documentation method. The sample for this research is basic industrial and chemical companies listed on the IDX from 2020 to 2022. The sample was selected using a purposive sampling method and 36 companies were collected. Testing was carried out using the multiple linear regression method using SPSS. The findings of the market adjustment model show that return on equity and company size have a significant influence on abnormal returns. Current Ratio does not have a significant influence on abnormal returns. This research has limitations regarding research variables and research year.